Support System for Tunnelling in Squeezing Ground of Qingling-Daba Mountainous Area: A Case Study from Soft Rock Tunnels. (3rd June 2019) - Wang, Xiuling; Lai, Jinxing; Garnes, Rodney Sheldon; Luo, Yanbin
Abstract : Tunnelling or undertaking below-ground construction in squeezing ground can always present many engineering surprises, in which this complicated geology bring a series of tunnelling difficulties. Obviously, if the major affecting factors and mechanism of the structure damage in these complicated geological conditions are determined accurately, fewer problems will be faced during the tunnel excavation. For this study, reference is made to four tunnel cases located in the Qingling-Daba mountainous squeezing area that are dominated by a strong tectonic uplift and diversified geological structures. This paper establishes a strong support system suitable for a squeezing tunnel for the purpose of addressing problems exhibited in the extreme deformation of rock mass, structure crack, or even failure during excavation phase. This support system contains a number of temporary support measures used for ensuring the stability of tunnel face during tunnelling. The final support system was constructed, including some key techniques such as the employment of the foot reinforcement bolt (FRB), an overall strong support measure, and more reserved deformation. Results in this case study showed significant effectiveness of the support systems along with a safe and efficient construction process. The tunnel support system proposed in this paper can be helpful to support design and provide sufficient support and arrangement before tunnel construction in squeezing ground.